From sensation to regulation: the diverse functions of peripheral sensory nervous system - Mei, Yixiao; Zhou, Bing-Lin; Zhong, Da; Zheng, Xuan-Jie; Deng, Yu-Tao; Yu, Lina; Jiang, Bao-Chun (Frontiers in Immunology, 2025)
The peripheral sensory nervous system (PNS) has been widely recognized for its role in the collection, processing, and transmission of sensory information, including thermal, mechanical, chemical, and proprioceptive stimuli. In recent years, there has been a growing scholarly interest in the PNS attributable to its multiple physiological and pathophysiological non-sensory roles in the organs it innervates. The PNS exerts regulatory functions within the organs it innervates through direct interactions with local cells or through microbe-nerve-cell interactions that differ from the traditional feedback regulatory modes used by the hormonal and sensory brain-sympathetic/parasympathetic systems. The release of the neuropeptide calcitonin gene related peptide (CGRP) by nerves, through its action on CGRP receptors in peripheral cells, constitutes a primary molecular axis for PNS regulation of organ cells, maintaining tissue homeostasis, facilitating pathological processes, and modulating innate and adaptive immunity. This review highlights the non-sensory functions of the peripheral sensory nervous system in various tissues and organs, focusing on phenotypes, molecular mechanisms and their significance, while also exploring future research directions, methodologies and potential preclinical studies aimed at targeting these pathways for the development of novel therapies.